KEBERHASILAN PROGRAM “YUK NABUNG SAHAM” OLEH BURSA EFEK INDONESIA DALAM MENINGKATKAN PENJUALAN INSTRUMEN PASAR MODAL DI INDONESIA - Rosmida Rosmida; Endang Sri Wahyuni (Inovbiz: Jurnal Inovasi Bisnis, 2017)
Abstract: Research entitled The Success of "Yuk Nabung Saham" Program by Indonesia   Stock   Exchange   in   Increasing   the   Sales   of   Capital  Market Instruments In Indonesia is a descriptive study aimed at knowing what exactly is the program Yuk Nabung Saham and how much investment people invest in Indonesia capital market in 2016 with the program Yuk Nabung Saham. Yuk Nabung Saham was launched on 12 November 2016 by the Vice-President of the Republic of Indonesia Mr. Muhammad Jusuf Kalla. Yuk Nabung Saham there is a campaign that invites the people of Indonesia to invest in the capital market through share saving. Currently there are 37 securities companies that have been working with the Indonesia Stock Exchange to join the Yuk Nabung Saham program. Data obtained from Indonesia's Financial Services Authority in 2013 and then compared with data in 2016. From these data recorded the increase in literacy and financial inclusion that initially 3.79% to 4.40% and0.11% to 1.25%. In addition, there is also an increase in the number of activeinvestors of Indonesian society in the Indonesian capital market which was originally 12.88% to 16.29%.